Allocating international loss and damage finance through national climate funds: Prospects for African LDCs - Mariya Aleksandrova; Washington Onyango Kanyangi; Assouhan Jonas Atchadé; Joanes Atela; Charles Tonui (German Institute of Development and Sustainability (IDOS), 2025)
The new loss and damage funding framework under the United Nations Framework Convention on Climate Change (UNFCCC) emphasises the importance of channelling support through national systems and mechanisms. This approach could prove particularly challenging for African least developed ountries (LDCs), which have been prioritised for support. These countries remain confronted with major challenges to access and utilise international climate finance, especially through direct access. National climate funds (NCFs) can have a potential role in delivering international loss and damage finance to African LDCs that is in line with their national priorities. NCFs can be defined as entities mandated to finance the implementation of national climate strategies and to manage and/or coordinate domestic and international sources of climate finance. NCFs can enhance the institutional capacities of countries by supporting the development of loss and damage strategies, facilitating access to international funding, aligning resource allocation with local priorities, and ensuring the effective tracking of loss and damage finance. This Policy Brief explores the role of NCFs in the evolving global loss and damage finance architecture with a focus on African LDCs. We examine the design features of five NCFs against criteria for assessing their relevance to support measures that address loss and damage. The studied NCFs are: the Benin National Fund for Environment and Climate, Ethiopia's Climate-Resilient Green Economy Facility, Burkina Faso's Intervention Fund for the Environment, the Mali Climate Fund and the Rwanda Green Climate Fund.
Keywords: 320; climate finance; loss and damage; least developed countries; UNFCCC; Fund for Responding to Loss and Damage